Risk factors for implant failure of custom-made acetabular implants in patients with Paprosky III acetabular bone loss and combined pelvic discontinuity - Fröschen, Frank Sebastian; Randau, Thomas M.; Gravius, Nadine; Wirtz, Dieter C.; Gravius, Sascha; Walter, Sebastian G. (Technology and health care, 2022)
BACKGROUND: Severe acetabular bone loss in revision total hip arthroplasty (RTHA), both with or without pelvic discontinuity, remains a great challenge in orthopaedic surgery. OBJECTIVE: The aim of this study was to evaluate risk factors for failure of custom-made acetabular implants in RTHA. METHODS: Seventy patients with severe acetabular bone loss (Paprosky Type III) and pelvic discontinuity, who required RTHA, were included in our study. All prostheses were constructed based on a thin-layer computed-tomography (CT) scan of the pelvis. The treatment was considered unsuccessful in the event of periprosthetic joint infection (PJI) or aseptic loosening (AL) with need for explantation of the custom-made acetabular implant. RESULTS: The average follow-up was 41.9 ± 34.8 months (range 1.5–120). Implant survival at last follow-up was 75.7% (53 of 70). Explantation was necessary in 17 cases (15 PJI; 2 AL). Previous PJI as reason for RTHA (p= 0.025; OR 3.56 (95% CI: 1.14; 11.21)), additional revision of femoral components (p= 0.003; OR 8.4 (95% CI: 1.75; 40.42)), rheumatoid disease (p= 0.039; OR 3.43 (95% CI: 1.01; 11.40)), elevated preoperative CRP > 15.2 mg/l (p= 0.015; AUC: 0.7) and preoperative haemoglobin < 10.05 (p= 0.022; AUC: 0.69) were statistically significant risk factors associated with treatment failure. Age and BMI were not statistically significant contributing to implant failure. CONCLUSION: Risk factors for treatment failure were a previous PJI, additional revision of femoral component, rheumatoid disease, elevated preoperative CRP and low preoperative haemoglobin. Awareness of these risk factors will help to improve future treatment standards.